The β-amylase PbrBAM3 from pear (Pyrus betulaefolia) regulates soluble sugar accumulation and ROS homeostasis in response to cold stress. (October 2019) - Zhao, Liangyi; Yang, Tianyuan; Xing, Caihua; Dong, Huizheng; Qi, Kaijie; Gao, Junzhi; Tao, Shutian; Wu, Juyou; Wu, Jun; Zhang, Shaoling; Huang, Xiaosan
Highlights: Subcellular localization assay indicates that PbrBAM3 is located in chloroplast. PbrBAM3 was responsive to various types of abiotic stresses, particularly cold. Transgenic tobacco and pear overexpressing PbrBAM3 showed better cold tolerance. Abstract: β -Amylase (BAM) is involved in sugar metabolism, but the role of BAM genes in cold tolerance remains poorly understood. Here, we report the identification and functional characterization of the chloroplast-localized BAM-encoding gene PbrBAM3 isolated from Pyrus betulaefolia . The transcript levels of PbrBAM3 were up-regulated under cold, dehydration and ABA, but repressed by maltose. Overexpression of PbrBAM3 in tobacco (Nicotiana tabacum ) and pear ( P. ussuriensis ) conferred increased BAM activity, promoted starch degradation after chilling treatments and enhanced tolerance to cold. Under the chilling stress, the transgenic tobacco and P. ussuriensis exhibited lessened reactive oxygen species (ROS) generation, higher levels of antioxidant enzymes activity, and greater accumulation of soluble sugars (specially maltose) than the corresponding wild type plants. Taken together, these results demonstrate that PbrBAM3 plays an important role in cold tolerance, at least in part, by raising the levels of soluble sugars capable of acting as osmolytes or antioxidants.